PENERAPAN PENDEKATAN PEMBELAJARAN BERBASIS MASALAH TERHADAP AKTIVITAS SISWA PADA KONSEP SISTEM PERNAPASAN MANUSIA - Siti Maryam Fadhilah Palestina (Program Studi Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Almuslim, 2014)
This study were aimed to know : Activity of students on the subject of human system respiratory using problem based learning strategy was compare by critical thinking skill of students using conventional learning. The study was conducted in SMA Negeri 4 Bireuen. The method used was experiment. The sample in this study were two classes is determined by cluster random sampling, consist of an exsperimental class (problem based learning) and the control class (conventional learning). The technique of analyzing data was conducted through t test. The conclusion of the research are significantly different both students activity who taught using problem based learning with students who taught using conventional learning. Key words: problem based learning, students activity, human system respiratory